Effect of Self-management Educational Program on Vision-related Quality of Life among Elderly with Visual Impairment - Ahmad Ghasemi; Hossein Karimi Moonaghi; Samira Mohajer; Seyed Reza Mazlom; Naser Shoeibi (Mashhad University of Medical Sciences, 2018)
Background: Visual impairment is one of the independent risk factors for falling among the elderly. Functional disabilities caused by vision disorders are the most common problems affecting the quality of life in this population. Therefore, vision self-management program (VSM) may be helpful for patients in reducing impairment and improving the quality of life. Aim: The present study aimed to investigate the effect of self-management educational program on the vision-related quality of life among the elderly with visual impairment. Method: This randomized clinical trial was conducted on 57 elderly people in Mashhad, Iran, in 2017. The participants were assigned into two groups of intervention (n=28) and control (n=29). The intervention group received a 6-week VSM as a 60-minute session per week, while the control group underwent the routine education in the clinic. Visual-related quality of life was measured using the 39-item National Eye Institute Visual Function Questionnaire immediately and two months after the intervention to implement home-based intervention. The data were analyzed in SPSS software, version 23. Results: The mean age of the participants in the intervention and control groups were 66.4±0.7 and 66.1±7.0 years, respectively. The repeated measures ANOVA test showed that the mean score of vision-related quality of life in the intervention group was significantly higher than that in the control group (P